Development of Accounting Pocket Book as Accounting Learning Media - Ningsih, Murti Wida; Lestari, Neta Dian; Pramika, Depi (Economic Education Analysis Journal, 2021)
This study used the Rowntree model with several stages such as: planning stage, development stage, and evaluation stage. This research is included in the Research & Development (R&D) research where the method used to produce a particular product and assess the product is by collecting data using an initial test (Pre-test) and a final test (Post-test). Collecting data in this study used observation, interviews, questionnaires, and tests. The data analysis technique used descriptive data analysis by assessing the product both from the media and the use of the product and assessing the scale used to find out the results of the product using Likert. With the stages of product testing by material experts, and media experts, so that the results of the study showed that accounting pocket books showed the validity of pocket books from material experts with an average result of 94% being in very valid criteria, media experts with an average result of 95% being in very valid criteria.The results of student comments and suggestions stage one by one, that the accounting pocket book was interesting and practical, while the small group stage with an average result of 89% was in very practical criteria and field test results were on average 85% in very practical criteria.